"Jantung Aktif, Hidup Produktif; Jantung Sihat Mudah Ibadah" - Mahfar, Nurulizzah; Abdul Shakor, Ameerah Su’ad; Ahmad Fuad, Mohd Hazim; Yasin, Siti Munira; Abdullah, Nik Nairan; Suddin, Leny Suzana; Xin Wee, Chen (Faculty of Medicine, 2024)
A vibrant health carnival themed “Jantung Aktif, Hidup Produktif” (Active Heart, Productive Life) and “Jantung Sihat, Mudah Ibadah” (Healthy Heart, Easier Worship) was held on 13 October 2024, at Masjid Al-Azhariah in Seksyen 18, Shah Alam, Selangor.